Many-dimensional covariant random fields on the commutative locally compact groups - Malyarenko, A.A.; Olenko, A.Ya.; Маляренко, А.А.; Оленко, А.Я. (Institute of Mathematics, NAS of Ukraine, 1992)
Homogeneous in the wide sense, covariant random fields on commutative local compact groups with values in finite-dimensional complex Hilbert spaces are considered. The general formula for the correlation operator of such a field is proved, as well as the spectral representation of the field itself in the form of a series of stochastic integrals with respect to orthogonal random measures.